Physical Activity, Screen Time and Sleep among Youth Participating and Non-Participating in Organized Sports - The Finnish Health Promoting Sports Club (FHPSC) Study - Mäkelä Kasper; Kokko Sami; Kannas Lasse; Villberg Jari; Vasankari Tommi; Heinonen Olli J; Savonen Kai; Alanko Lauri; Korpelainen Raija; Selänne Harri; Parkkari Jari (United States, 2022)
Objectives: The aim of this Health Promoting Sport Club (HPSC) study was to compare physical activity (PA), sleep time and screen time (ST) between sports club participants (n = 1200) and non-participants (n = 913).
Design: A cross-sectional survey design was employed to assess PA, sleep and ST of adolescents.
Methods: Information on these was collected from 14 to 16 year old adolescents (1200 sport club participants and 913 non-participants) through a standardized questionnaire.
Results: Boys were more physically active than girls and met the PA guidelines more often than girls (p < 0.001). The proportion of youth reaching the PA guidelines was significantly higher among youth participants in organized sports (24.3%) compared to non-participants (14.5%) (p < 0.001). Sport club participants slept longer (1.25 hours) during weekends than non-participants (p < 0.001). Girls reported less ST than (30 minutes) boys (p < 0.001). Sport club participants reported less ST than non-participants (0.5 hours) (p < 0.001).
Conclusions: Youth participating in organized sports met the recommendations for PA, ST and sleep more often than nonparticipants, supporting sports clubs’ contribution to health promotion. At the same time, only minor portion of sporting youth met the recommendations, therefore more attention should be focused on sport club participants’ PA, sleep and ST especially in coaching.